If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 17y = 5 Solving 11x + 17y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17y' to each side of the equation. 11x + 17y + -17y = 5 + -17y Combine like terms: 17y + -17y = 0 11x + 0 = 5 + -17y 11x = 5 + -17y Divide each side by '11'. x = 0.4545454545 + -1.545454545y Simplifying x = 0.4545454545 + -1.545454545y
| g^2-4g-45= | | 16x^2-4=1 | | 9+19m-6=6m+99-3m | | 5(x+3)=5(x+5) | | b^2+20b+36= | | 64x=x^2 | | 8x-4(-5-2)=12x | | 12(t-4)+6t=6(3t+5)-9 | | (5x)*(2y)= | | 6(x+1)=-3(2-x)+3x | | -x+4y=8 | | 6n+4-3n-3=0 | | 0.9(x+30)+0.9x=108 | | 5m+3m^2=0 | | 2w^2+4w-1152=0 | | y-5=-3(x-17) | | d^2-7d+10= | | x^2-15x+(56.25)=-26 | | 6(x+2)=6(x+5) | | (-x)*(6y)= | | a^6+b^6c^6= | | y^2+13y+30= | | 8x-7=10x+5 | | 0.6(x+100)+0.8x=109 | | -4a*2c= | | y-b=mx | | 5+7=x | | wx=y | | 12m^2n^2+8mn-1= | | -4a=-14a | | Y=11x+5 | | 3a*6b= |